PA10 What i need you to know. building a collaborative communication tool. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Abbott, Aine; Watson, Max; Gingles, Jenny; Brown, Scott; Brennan, Jill; Scott, Keith; McCrory, Bernadine; Marley, Anne Marie; Dorman, Laurence; McCullagh, Rose; Fannin, Shauna; Scott, Keith; et al.
Abstract : Background: During strategy consultation in Northern Ireland an "End of Life Care Passport" was suggested as a way to address myriad communication difficulties involved in living with evolving illness. Aim: To build a patient-owned communication tool to facilitate important conversations and capture key information as health changes. Methods: Participatory action methods used to engage service users, carers, patient advocates, and healthcare professionals. Views harnessed via: face to face, email, telephone, via series of workshops. Iterative process of drafting, dissemination, evaluation, re drafting. Pilot version launched (350 disseminated): used for a 3 month evaluative period by 3 groups: living with dementia, with motor neurone disease, with advanced respiratory illness. Feedback widely sought from participating individuals and groups. Results: The emergent tool 1 very different from originally envisaged. Key issues include widespread rejection of "End of Life Care Passport" (felt to be professionally based perspective); very high level of engagement with the process, imperative to develop a tool which focusses on language and communication needs of patient and carers rather than professionals. Emergent tool contains ten sections and brief explanatory content. Housed as A5 portable ring binder (e-version suggested), updated collaboratively by patient, carers, key supporters, professionals. Conclusion: Patients and carers face multiple communication difficulties negotiating changing health. At particular risk are those with rare illness and those whose capacity is limited due to illness, language or cultural barriers. There is a role for a communication tool which houses key evolving information, is completed collaboratively and patient owned and controlled. Reference: http://www.rcgp.org.uk/rcgp-near-you/rcgp-northern-ireland/my-healthcare-passport.aspx